2010
DOI: 10.1074/jbc.c110.154658
|View full text |Cite
|
Sign up to set email alerts
|

ArPIKfyve Regulates Sac3 Protein Abundance and Turnover

Abstract: The mammalian phosphatidylinositol (3,5)-bisphosphate (PtdIns(3,5)P 2 ) phosphatase Sac3 and ArPIKfyve, the associated regulator of the PtdIns3P-5 kinase PIKfyve, form a stable binary complex that associates with PIKfyve in a ternary complex to increase PtdIns(3,5)P 2 production. I41T rapid loss. Together, our data indentify a novel regulatory mechanism whereby ArPIKfyve enhances Sac3 abundance by attenuating Sac3 proteasome-dependent degradation and suggest that a failure of this mechanism could be the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 25 publications
2
32
0
Order By: Relevance
“…The unaffected father was found to have both the FIG4 intronic and the LITAF variants – excluding the LITAF mutation as pathogenic. The FIG4 c.122T>C variant (I41T) is one of the most common variants in patients with CMT4J, and leads to rapid degradation of the FIG4 proteins 4. The intronic FIG4 variant was recently reported in a person with CMT4J, also with the I41T variant5 and was absent in >60,000 exomes [exac.broadinstitute.org].…”
Section: Resultsmentioning
confidence: 99%
“…The unaffected father was found to have both the FIG4 intronic and the LITAF variants – excluding the LITAF mutation as pathogenic. The FIG4 c.122T>C variant (I41T) is one of the most common variants in patients with CMT4J, and leads to rapid degradation of the FIG4 proteins 4. The intronic FIG4 variant was recently reported in a person with CMT4J, also with the I41T variant5 and was absent in >60,000 exomes [exac.broadinstitute.org].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the PtdIns(3,5) P 2 synthesis pathway described in yeast is conserved in human, with PIKfyve interacting with multiple partners [108]. This interaction is indirect and requires the adapter protein ArPIKfyve/VAC14 to stabilize the complex and stimulate PIKfyve activity [109]. As in yeast cells, VAC14 serves as a platform regulating PtdIns(3,5) P 2 synthesis by interacting directly with PIKfyve, FIG4/SAC3 and VAC7 to fine tune the regulation of PtdIns(3,5) P 2 levels [109,110].…”
Section: Ptdins(35)p2 a Regulator Of Endosome-lysosome Traffickingmentioning
confidence: 99%
“…This interaction is indirect and requires the adapter protein ArPIKfyve/VAC14 to stabilize the complex and stimulate PIKfyve activity [109]. As in yeast cells, VAC14 serves as a platform regulating PtdIns(3,5) P 2 synthesis by interacting directly with PIKfyve, FIG4/SAC3 and VAC7 to fine tune the regulation of PtdIns(3,5) P 2 levels [109,110]. Mutation in the FIG4 gene causes Charcot-Marie-Tooth neuropathy [111], and the Mtmr2 knock-out mice model for the disease has elevated PtdIns(3,5) P 2 levels [112].…”
Section: Ptdins(35)p2 a Regulator Of Endosome-lysosome Traffickingmentioning
confidence: 99%
“…Further analysis demonstrated that the instability of the I41T protein is a consequence of impaired binding to the VAC14 scaffold protein. The level of FIG4-I41T is also very low in patient fibroblasts, and can be increased by inhibition of degradation by the proteasome pathway (Lenk et al, 2011; Ikonomov et al, 2010). …”
Section: The Human Disease Mutation Fig4-i41t In Transgenic Micementioning
confidence: 99%